Plant Growth and Regulation Alterations to Sustain Unfavorable Conditions - Ratnadewi, Diah (IntechOpen, 2018)
Plant Growth and Regulation - Alterations to Sustain Unfavorable Conditions consists of five chapters written by scientists from different parts of the world, who are experts in their respective focuses of research. The topics cover the physical growth and physiological and genetic alterations in plants, particularly under environmental stress conditions. The storyline of this book starts from the plant community, followed by cellular and ultrastructural phenomenes occurring within the plant in its interaction with the environment, and ends with elucidation of chloroplast's DNAs, their transfer to the nucleus, and the genetic engineering technology applicable for plant adaptation to changing environmental conditions. This book is aimed at attracting the attention of students, teachers, as well as scientists who have a similar focus of study or interest. It contains advanced studies in the respective chapters.